PENGARUH TINGKAT SUHU PEMANASAN PADA BERBAGAI STRAIN AYAM PETELUR YANG BERBEDA TERHADAP PROFIL FRAKSI PROTEIN TELUR DENGAN MENGGUNAKAN SDS â PAGE (Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis ) - Juniarto, Muhammad Deny (Universitas Kanjuruhan Malang, 2013)
The research had been conducted at August 2011 in Biology Molecular Laboratory of Mathematic and Natural Science Faculty and Central Laboratory of Brawijaya State University. The aim of the research was to know whole eggprotein characteristic of hen eggs from diferent strain and influence of heating temperature to the change of protein characteristic. The material of the research was infertile eggs from different strain breeds namely Lohman hen egg, Hubbardhen egg and Isa Brown hen egg. The used method analytical study such as experiment of several treatment effect. The treatment were: control (P0) unheated egg; the first treatment (P1) egg heated at 63 ºC, the second treatment (P2) egg heated at 100 ºC. The variable measured was protein characteristic. The ovalbumin is a heat stable protein which that detected as thiny band after heating treatment up to 100 ºC. The characterized protein band of eggs yolk was Apo LDL, pd-LDL, α-phosvitin, vitelin major, phosvitin minor, and vitelin minor. The Lohman hen egg is almost detected all kinds of protein.Key words: protein characteristic, strains hen egg, whole egg.